A Model and Application for Estimating Completeness of Registration - Berghold, A.; Stronegger, W.-J.; Wernecke, K.-D. (Methods of Information in Medicine, 2001)
Completeness of population-based registration systems is recognized to be an important aspect of the quality of information in registries which has to be examined. In this paper a model is presented which was used to estimate completeness of reporting of Down syndrome data notified to the Styrian Malformation registry between 1985-92. The model introduced is based on the two-source capture-recapture method allowing for time-varying parameters. For estimation of the parameters a discrete-time filtering algorithm was developed. For the used data set, an estimate of completeness derived from this model was in good agreement with an independent estimator based on demographic data and maternal age-specific Down syndrome risks whereas the usual two-source capture-recapture method gave a higher estimate.
Keywords: Capture-Recapture Methods; Dynamic Model; Registration; Down Syndrome